2017
DOI: 10.1159/000477872
|View full text |Cite
|
Sign up to set email alerts
|

Activities of MSCs Derived from Transgenic Mice Seeded on ADM Scaffolds in Wound Healing and Assessment by Advanced Optical Techniques

Abstract: Background/Aims: Bone marrow Mesenchymal stem cells (MSCs) are promising for promoting cutaneous wound healing through reinforcing cellular processes. We evaluated the effect of GFP-tagged MSCs transplantation on skin regeneration in excisional wounds in mice. Methods: MSCs from GFP-labeled transgenic mice were co-cultured with acellular dermal matrix (ADM) scaffolds, and MSC-ADM scaffolds were transplanted into surgical skin wounds of BALB/c mice. After implantation, the survival and behavior of MSCs were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Notably, previous studies have reported that the actin cytoskeleton is regulated by p53 via activation of HtrA2/Omi [56], which hampers cell invasion. However, our studies further characterized the mechanism by which HtrA2/Omi disturbs actin homeostasis [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have reported that the actin cytoskeleton is regulated by p53 via activation of HtrA2/Omi [56], which hampers cell invasion. However, our studies further characterized the mechanism by which HtrA2/Omi disturbs actin homeostasis [57]. …”
Section: Discussionmentioning
confidence: 99%
“…GFP + BMSCs were obtained as previously reported by our group [ 30 ]. BMSC sheets were prepared by plating 1.5 × 10 5 of third passage cells on culture dishes (six-well plates, Corning).…”
Section: Methodsmentioning
confidence: 99%
“…However, these authors argued that activated NR4A1 due to high-fat diets mediates Drp1 phosphorylation and represses Bnip3 transcription, leading to fission activation and mitophagy inhibition. Other signaling pathways may also be involved in simultaneously regulating fission and mitophagy [70,71]. In cardiac microvascular ischemia reperfusion, DUSP1 has been shown to repress fission and recuse mitophagy via the JNK pathway [17,72].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%